2019
DOI: 10.12659/msmbr.914570
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR-2 Is in a State of Activation in Hair Follicles, Sebaceous Glands, Eccrine Sweat Glands, and Epidermis from Human Scalp: An In Situ Immunohistochemistry Study of Phosphorylated VEGFR-2

Abstract: Background Recent research reports that VEGFR-2 is expressed in the whole hair follicle, sebaceous glands, eccrine sweat glands, and epidermis. However, phosphorylated VEGFR-2 was not found, and it could not be ascertained whether the activated form of VEGFR-2 actually participates in the biological control of epidermal appendages. In this study we aimed to determine whether the VEGFR-2 pathway is directly involved in the daily regulation of epidermal appendages biology. Material/Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…VEGF from dermal papilla attracts adjacent blood vessel to supply vascular-derived growth factors to the hair follicles. VEGF also stimulates adjacent cells, such as outer root sheath cells, matrix progenitor cells, sebaceous glands, sweat glands, and epidermis to make the hair follicle fully matured and the hair shaft differentiated [34]. As shown in Figure 5, the protein level of VEGF was up-regulated by the D-panthenol treatment.…”
Section: D-panthenol Stimulated Vegf Expression In Cultured Hdpcsmentioning
confidence: 92%
“…VEGF from dermal papilla attracts adjacent blood vessel to supply vascular-derived growth factors to the hair follicles. VEGF also stimulates adjacent cells, such as outer root sheath cells, matrix progenitor cells, sebaceous glands, sweat glands, and epidermis to make the hair follicle fully matured and the hair shaft differentiated [34]. As shown in Figure 5, the protein level of VEGF was up-regulated by the D-panthenol treatment.…”
Section: D-panthenol Stimulated Vegf Expression In Cultured Hdpcsmentioning
confidence: 92%
“…Sebaceous glands are complex structures, and their genesis and homeostasis are dependent on mesenchymal signals, including EGFR and VEGF, and regulatory T cells that are also capable of inducing follicularderived and epidermal-derived sebaceous glands from resident stem cells. [21][22][23][24] The sebaceous glands are directly connected to the infundibular canal through cuticular-lined sebaceous ducts forming an axis representing a complex homeostatically controlled structure. Sebum production is more prominent than trichogenesis in sebaceous follicles.…”
Section: Structural and Functional Homeostasis Of Hair Follicles And ...mentioning
confidence: 99%
“…The PD-1/PD-L1, VEGF/ VEGFR, and EGFR/amphiregulin axes govern multiple pathways of signal transduction. [22][23][24][25] These pathways are widely expressed and are key in maintaining skin homeostasis, including those related to the follicular infundibulum and sebaceous glands. Repair Tregs have been identified that are integrated to these signal transduction pathways forming a complex wound healing and follicular repair system encompassing infundibular committed stem cell.…”
Section: Biological Antitumor Inhibitors and The Paradoxical Developm...mentioning
confidence: 99%
“…Insulin-like growth factor 1 (IGF-1), a well-known hair growth-promoting factor, controls the hair growth phase and hair shaft differentiation, in addition to preventing anagen-to-catagen transition [ 17 ]. Additionally, vascular endothelial growth factor (VEGF), which is widely recognized as a hair growth-promoting factor, influences hair shaft differentiation in the hair growth phase by promoting the proliferation and differentiation of hair root cells for hair shaft formation [ 18 ]. Transforming growth factor-beta 1 (TGF-β1) inhibits hair shaft formation and development by inducing apoptosis, increasing telogen hair follicles, and promoting the transition of growing hair follicles into catagen hair follicles [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%